Oligosaccharides from Sargassum thunbergii inhibit osteoclast differentiation via regulation of IRF-8 signaling - Weihua Jin; Fen Chen; Qiufu Fang; Genxiang Mao; Yizhong Bao (Experimental Gerontology, 2023)
Osteoporosis (OP) is a systemic bone degenerative disease characterized by low bone mass and deteriorated microarchitecture of bone tissue, causing high morbidity and mortality rates. Bone resorption by overactivated osteoclasts (OCs) is the main cause of osteoporosis. Glucuronomannan and its oligomers (Gs) and their sulfated derivatives (SGs) were previously prepared. The anti-osteoporosis activities of these glycans were evaluated. Firstly, we determined the viability of RAW264.7 by CCK-8 test. Nextly, we investigated the inhibitory effects of Gs and SGs on the differentiation of RAW264.7 cells into OCs using tartrate-resistant acid phosphatase (TRAP) staining, F-actin ring staining, qualitative reverse-transcription polymerase chain reaction(qRT-PCR) and western blotting. TRAP staining revealed that Gs significantly blocked RANKL-induced OC generation while SGs did not exhibit this ability. F-actin staining assays demonstrated that Gs inhibits RANKL-induced actin ring formation. qRT-PCR analyses indicated that Gs dose-dependently inhibited the expression of OCs marker genes including Trap, NFATc1, c-Fos, DC-Stamp and ATP60 during the differentiation process, while SGs did not suppress. Regarding the mechanism of Gs, it was found that Gs suppressed osteoclastogenesis via inhibiting the degradation of IRF-8 and interfering with NF-κB pathway activation. Together, these results suggest that Gs have the ability to inhibit osteoclastogenesis by modulating IRF-8 signaling.